중등학교에서 Donald W. Oliver와 James P. Shaver의 법리적 교수전략을 활용한 공공 정책에 관한 정치적 논쟁 가르치기 - 배영민(Yung-Min Bae) (교과교육학연구, 2022)
이 연구는 Donald W. Oliver와 James P. Shaver(1966)가 하버드 사회과 프로젝트에서 개발한 공공 정책을 둘러싼 정치적 논쟁을 분석하는 ‘법리적 교수전략’을 고찰한다. 우리가 법리적 교수전략을 제대로 이해하기 위해서는 법리적 교육과정의 사상적 기반을 알아야 한다. 그래서 이 연구는 먼저, 법리적 교육과정의 사상적 기반이 되는 고전적 자유주의 사상을살펴본다. 그런 다음, 법리적 교수전략의 법리적 토대가 되는 궁극의 가치로서 개인의 존엄과 일반적 가치들, 정치적 논쟁 분석의 윤리적 원리로서 민주적 입헌주의, 그리고 정치적·윤리적 문제들의 해결 방법으로서 법적 결의론(legal casuistry)을 각각 논의한다. 이를 바탕으로, 이 논문은 공산주의 서적의 검열을 예로 들어 법리적 교수전략의 적용 사례를 상세하게 설명한다. 또한, 법리적 교수전략이 지니는 의의와 한계를 논의한다. 그리고 결론에서 원론적인 수준에서 법리적 교수전략을 우리나라의 중등학교 사회과 수업에 확산하기 위한 몇 가지 과제들을 언급한다. This study examines the jurisprudential teaching strategy that analyzes the political controversy over public policies proposed by Donald W. Oliver and James P. Shaver (1966) in the Harvard Social Studies Project. In order to properly understand the jurisprudential teaching strategy, it is required to understand the ideological basis of the jurisprudential curriculum. So, this study first examines the classical liberal ideas that are the basis of the jurisprudential curriculum. Then, the discussion is made on individual dignity as the ultimate value and general values, democratic constitutionalism, and legal casuistry that serve as the jurisprudential basis for the jurisprudential teaching strategy. Based on this, this paper explains in detail the application of the jurisprudential teaching strategy, taking censorship on communist books as an example. In addition, the significance and limitations of the jurisprudential teaching strategy are discussed. In conclusion, it suggests several tasks to spread the jurisprudential teaching strategy in social studies classes in secondary schools. KCI Citation Count: 0